The Objection to The Claim of Meeting The Prophet Muḥammad in a State of Awakedness According to Muḥammad al-Shinqīṭī - Abdul Muthalib (Refleksi: Jurnal Kajian Agama dan Filsafat, 2012)
This paper deals with the reaction of al-Shinqīṭī towards this latter way of mystical vision, particularly in the case of Aḥmad al-Tijānī. For al-Shinqīṭī, sufis’ claim of having a fully consciousness physical contact with the Prophet after his death is impossible because nothing, whether religious or rational proofs, can sustain it. The extreme case of such claim is expressed by Aḥmad al-Tijānī who, insists that a sufi (ṣūfī) can really see the Prophet with his physical eyes. In al-Tijānī’s opinion, the ability of the physical eyes to see the Prophet when awake was a common trait of those who attained the status of pole (quṭb).DOI: 10.15408/ref.v13i3.902